2017
DOI: 10.1002/andp.201600254
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogap in the Eliashberg approach based on electron‐phonon and electron‐electron‐phonon interaction

Abstract: The properties of the superconducting and the anomalous normal state were described by using the Eliashberg method. The pairing mechanism was reproduced with the help of the Hamiltonian, which models the electron-phonon and the electron-electron-phonon interaction (EEPh). The set of the Eliashberg equations, which determines the order parameter function (ϕ), the wave function renormalization factor (Z), and the energy shift function (χ ), was derived. It was proven that for the sufficiently large values of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Surprisingly, it was found that, in oxide ceramics, the correlation length is some orders of magnitude less than that in traditional metal superconductors while the ratio of the energy gap to the temperature of superconducting transition is much greater [3]. The current status of research can be found in books and reviews [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, it was found that, in oxide ceramics, the correlation length is some orders of magnitude less than that in traditional metal superconductors while the ratio of the energy gap to the temperature of superconducting transition is much greater [3]. The current status of research can be found in books and reviews [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Above T C , the values of ϕ (T ) are declining much faster, while for T = 183.5 K, we observe the first order phase transition instead of the second order phase transition. Note that the change in the nature of the phase transition is induced by the applied approximations-the correct type of the phase transition is predicted on the Eliashberg equations level [36]. Interestingly, the value of the temperature, at which the transition occurs, is well defined and can be properly interpreted physically as will be discussed in the next section.…”
Section: Formalismmentioning
confidence: 91%
“…In the presented paper, we will show that beginning from the Eliashberg equations, presented in [36], one can get the generalized mean-field model. Next, we will derive the analytical formulas for the most important thermodynamic parameters of the superconducting state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that the four-electron term would appear in the second order of this expansion. One needs to mention that the problem of the four-fermion interaction in superconductors was investigated in a series of papers by Szczȩśniak et al [14][15][16]. In some of them, the Eliashberg formalism was applied in order to deal with cuprates as systems with strong coupling of electrons to phonons.…”
Section: The Modelmentioning
confidence: 99%